Corrigendum: Blood, sweat and tears: a review of non-invasive DNA sampling - Lefort, Marie-Caroline; Cruickshank, Robert H.; Descovich, Kris; Adams, Nigel J.; Barun, Arijana; Emami-Khoyi, Arsalan; Ridden, Johnathon; Smith, Vikki R.; Sprague, Rowan; Waterhouse, Benjamin; Boyer, Stéphane (Peer Community Journal, 2022)
In the original article,Box 1 was not printed in its entirety, and two references were badly quoted in page 3 of the pdf and were missing in the reference list.